AKUNTABILITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) DI DESA COMPANG LONI KECAMATAN RANA MESE KABUPATEN MANGGARAI TIMUR - Dandur, Natalia Fitriani; Nikson Tameno,; Aldarine Molidya, (Journal of Innovation Research and Knowledge, 2025)
The purpose of this study is to explain the accountability of the management of the Village Revenue and Expenditure Budget (APBDes) in Compang Loni Village, Rana Mese District, East Manggarai Regency. This study uses a qualitative descriptive approach by conducting interviews with village apparatus inmates and also 25 community representatives. The techniques used in this study are interview, observation and documentation techniques. Based on the Regulation of the Minister of Home Affairs Number 20 of 2018, there are several stages in village financial management, including the planning stage, implementation stage, administration stage, reporting stage and accountability stage. The results of this study indicate that the accountability of the management of the Village Revenue and Expenditure Budget (APBDes) in Compang Loni Village has not been implemented optimally in accordance with Permendagri Number 20 of 2018 concerning Village Financial Management.